0908 The Impact Of Adenotonsillectomy On Obstructive Sleep Apnea In Children With Trisomy 21: A Retrospective Cohort Study. (27th May 2020) - Platt, J; Adeleye, A; Nettel-Aguirre, A; Chugh, A; Yunker, W
Abstract: Introduction: Obstructive sleep apnea (OSA) has a prevalence of 1 - 5.7% in the general pediatric population. In children with Trisomy 21 (T21), OSA is estimated to be much higher, at 30-60%. The medical consequences of untreated OSA may be significant, therefore it is worthwhile to explore treatment options. Adenotonsillectomy (AT) is often the first line treatment in children, including those with T21. However, success rates of AT in patients with T21 is more variable, and postoperative complications can be higher. The aim of this study was to determine the impact of AT on the apnea hypopnea index (AHI) in patients with Trisomy 21. Methods: A retrospective cohort study was conducted by reviewing children with T21 and the following criteria: 1) 0 to 18 years of age, 2) AT completed between January 2010 to December 2015, 3) pre- and post-operative polysomnogram (PSG). Data extraction included demographics, details of PSG both prior to and after surgery including severity of sleep apnea and oxygen levels, type of surgery, and surgical complications. Results: Our sample consisted of 64 subjects. Mean pre-operative AHI was 32.2, while mean post-operative AHI was 8.0, for a difference of 21.7 (p = 0.0001). Mean pre-operative oxygen saturation was 92.5, while mean post-operative oxygen saturation was 93.7, for a difference of 1.2 (p = 0.01). There were 10 post-operative emergency room visits (15.3%), 2 admissions to hospital (3.1%) and 2 repeat surgeries for post-operative bleeding (3.1%). Conclusion: Preliminary findings of this study show a statistically significant improvement in OSA severity as determined by change in AHI and mean oxygen saturations post AT in children with T21. Complication rates were low. Further data collection and analysis is underway. Support: None.